2021
DOI: 10.1002/smsc.202100016
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Cyano‐Substituted Aromatic Blocks into Naphthalene Diimide‐Based Copolymers: Toward Unipolar n‐Channel Field‐Effect Transistors

Abstract: The unipolar n‐type polymeric semiconductors are crucial for the development of complementary inverters and complementary logic circuits. To achieve this target, the polymer skeleton should be electron‐deficient, which guarantees the energy‐level alignment between the lowest unoccupied molecular orbital energy level of polymeric materials and the work function of electrode, further permitting effective electron injection. Different from the introduction of the sp2‐hybridized nitrogen atoms and fluorine atoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The two dibrominated electron-accepting monomers f-BTI2g-2Br and f-BSeI2g-2Br, and the distannylated cyanated selenophene-vinylene-selenophene donor comonomer SVSCN-2Sn were prepared according to previously reported procedures by our group and the others. [53,55,56] After a typical Soxhlet extraction process-based purification, the product polymers were obtained and characterized by gel-permeation chromatography (room temperature, chloroform as eluent), showing comparable number-average molecular weights (M n s) and polydispersity indices (PDIs) of 9.1 kDa/1.7 and 8.0 kDa/1.7 for f-BTI2g-SVSCN and f-BSeI2g-SVSCN (Figure S1, Supporting Information), respectively. It is worth noting that the M n s of both selenopheneincorporated polymers are relatively lower compared with those of their all-thiophene-based polymer, f-BTI2g-TVTCN (see structure in Scheme 1, M n /PDI = 28.3 kDa/4.8).…”
Section: Resultsmentioning
confidence: 99%
“…The two dibrominated electron-accepting monomers f-BTI2g-2Br and f-BSeI2g-2Br, and the distannylated cyanated selenophene-vinylene-selenophene donor comonomer SVSCN-2Sn were prepared according to previously reported procedures by our group and the others. [53,55,56] After a typical Soxhlet extraction process-based purification, the product polymers were obtained and characterized by gel-permeation chromatography (room temperature, chloroform as eluent), showing comparable number-average molecular weights (M n s) and polydispersity indices (PDIs) of 9.1 kDa/1.7 and 8.0 kDa/1.7 for f-BTI2g-SVSCN and f-BSeI2g-SVSCN (Figure S1, Supporting Information), respectively. It is worth noting that the M n s of both selenopheneincorporated polymers are relatively lower compared with those of their all-thiophene-based polymer, f-BTI2g-TVTCN (see structure in Scheme 1, M n /PDI = 28.3 kDa/4.8).…”
Section: Resultsmentioning
confidence: 99%
“…8). 125 Yu and co-workers attempted to achieve room-temperature stable MR response in OSVs using ambipolar P61 and P62 . 126 The results revealed that longer alkyl side chains on the NDI unit decreased MR values.…”
Section: Semiconducting Polymers Based On Diarylethylene Unitsmentioning
confidence: 99%
“…These undesirable issues make p-type-only circuits more attractive and it is welcomed to find a unipolar circuit design for OFET-based XOR gates. [36] To address these challenges, we adopted a unipolar-transistorbased XOR gate design and excavated its postfabrication tunability, which is very important for solving the device instability Organic field-effect transistor (OFET)-based circuits require stable device performance. However, OFETs are suffering from process variation and environmental instability, which limits circuit performance.…”
mentioning
confidence: 99%